Does private supplementary tutoring matter? The effect of private supplementary tutoring on mathematics achievement. (July 2021) - He, Yahan; Zhang, Yuhuan; Ma, Xiao; Wang, Lidong
Highlights: Participation in private supplementary tutoring has been a global educational phenomenon and is especially prevalent in eastern Asia. During summer vacation, participation in private tutoring has a significant positive effect on students' mathematics achievement. There is a non-significant effect during school semester. The different instructional coherence of the two kinds of private tutoring could partly explain the results. Abstract: Participation in private supplementary tutoring (PT) is a global educational phenomenon especially prevalent in East Asia. This study conducted a student-report questionnaire, collected school reports of mathematics achievement to track retrospective longitudinal variations of PT over half a year, and obtained an analysis of the impact of PT participation on mathematics achievement during the school semester and summer vacation. Results show that, during summer vacation, students' participation in PT has a significant positive effect on their mathematics achievement; however, the effect is insignificant during the school semester. The findings enhance the knowledge about the effectiveness of PT and summer learning.